IMF Conditionality and Country Ownership of Programs - Khan, Mohsin (IMF Working Papers; Working Paper ;, 2001)
The paper uses finance and agency theory to establish two main propositions: First, that the conditionality attached to adjustment programs supported by the IMF is justified. Second, that ownership of programs by the borrowing country is crucial for their success. Hence, since both IMF conditionality and country ownership are necessary, the task is one of designing conditionality to maximize program ownership, subject to providing adequate safeguards for IMF lending. The paper discusses some recent proposals for enhancing ownership, and in particular, makes a case for incorporating floating tranches and outcomes-based conditionality in IMF-supported adjustment programs.